en - Miraza, Farahiyah Hafilah; Hidayati, Hidayati (e-Journal of Linguistics; Vol 16 No 2 (2022): ejl-July, 2022)
The issue that will be examined in this research is how conflicts portrayed in the novel The Trial by Franz Kafka. The aim of this research is to analyze and describe the external conflict found in the novel. The research problems of this research are: First, is about the external conflicts found in the novel and how it is portrayed, second, is to reveal the most dominant type of external conflict found in the novel. The method of analysis used in this research is the qualitative research method, it is analyzed based on the theory of conflict by Tennyson (1967) with the approach of psychological literature. The findings of this research are, 1.  There are two kinds of external conflicts found in the novel. 2.  Man Vs. Man is the most dominant conflict found in the novel, with the calculation using the theory of Anas (2008) with the result; Man Vs. Man (71,42%) and 2. Man Vs. Society (28,57%).